A blessing for humanity - Abd Razak, Dzulkifli (2010)
Last week, Muslims the world over remembered the birth of the Prophet Muhammad (peace be upon him) as a sign of respect for a person who has shaped much of the history of the world. Authors such as Michael Hart regarded him as exemplary for this reason. Hart listed the prophet in his book entitled The 100: A Ranking Of The Most Influential Persons In History (2000). The prophet is among the 11 religious leaders chosen, apart from scientists and inventors (37), political and military leaders (30), philosophers (14), artistic and literary figures, and explorers.